Longitudinal analysis of generic substitution - Dalen, Dag Morten; Locatelli, Marilena; Strøm, Steinar 1942- (CESifo working papers, 2010)
Using an extensive longitudinal dataset extracted from the Norwegian Prescription Database (NorPD) containing all prescriptions written in the period January 2004 to June 2007, we selected two particular drugs (chemical substances) used against cholesterol. The two brand-name products on the Norwegian markets were Provachol (atc code C10AA03) and Zocor (atc code C10AA01). The generics are Provastatine and Simastatine. The model accounts for taste persistence and is estimated on panel data. We find that prices have a negative impact on transitions in the sense that an increase in the brand price will reduce the transition from generics to brand and likewise an increase in the generic price will reduce the transition from brand to generics.